2018
DOI: 10.2147/cia.s154717
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptability of technology for community-dwelling older adults with mild cognitive impairment and dementia: a systematic literature review

Abstract: BackgroundThe objective of this review was to obtain an overview of the technologies that have been explored with older adults with mild cognitive impairment and dementia (MCI/D), current knowledge on the usability and acceptability of such technologies, and how people with MCI/D and their family carers (FCs) were involved in these studies.Materials and methodsPrimary studies published between 2007 and 2017 that explored the use of technologies for community-dwelling people with MCI/D were identified through f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 53 publications
(161 reference statements)
5
120
0
1
Order By: Relevance
“…Welfare technologies' impact and consequences for safety, independence and the ability to stay at home Overall, the participants in our study were positive to welfare technology and wanted to use it more because of the feeling of safety it gave them and because it could help them to continue to live an independent life at home, as supported by ndings from other studies (5,20,21). For example use of safety alarms enabled participants to keep doing daily activities without worrying about falling, which is in line with a nding from a study by Stokke (23).…”
Section: Conditions and Challenges For Involvement And Decision Makingsupporting
confidence: 71%
See 1 more Smart Citation
“…Welfare technologies' impact and consequences for safety, independence and the ability to stay at home Overall, the participants in our study were positive to welfare technology and wanted to use it more because of the feeling of safety it gave them and because it could help them to continue to live an independent life at home, as supported by ndings from other studies (5,20,21). For example use of safety alarms enabled participants to keep doing daily activities without worrying about falling, which is in line with a nding from a study by Stokke (23).…”
Section: Conditions and Challenges For Involvement And Decision Makingsupporting
confidence: 71%
“…The goal of using welfare technology is to strengthen individuals' ability to manage for themselves in everyday life and cope with their life situation, preferably in their own homes (20)(21)(22). Moreover, the use of welfare technology comes with an assumption of increased safety for service users and their next of kin (5,23).…”
Section: Welfare Technologymentioning
confidence: 99%
“…The ethical aspect becomes even more evident in relation to older adults having reduced decision-making ability, especially when CRO was discussed in relation to vulnerable older adults suffering from cognitive impairment. In contrast to these findings, a relatively optimistic view of technologies to support people with dementia in everyday life is presented in a recently published review [69]. From the professional caregivers' perspective, there is a possibility that care robots are regarded as a threat to the fundamental values of care.…”
Section: The What Aspect Of Cromentioning
confidence: 99%
“…Based on the results from a systematic review [18] focusing on health outcomes and efficacy of mHealth applications in adults with cognitive impairment, the evidence for improving health with the use of mHealth applications is of limited quality. Few studies [19] have reported on the consequences of technology use concerning older adults´QoL. Therefore, the aim of this study was to describe perceptions of mHealth and its impact on HRQoL among older adults with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%